Physical performance is affected by players' position, game location, and substitutions during official competitions in professional championship English football - Chaize, C.; Allen, M.; Beato, M. (The Journal of Strength and Conditioning Research, 2024)
This study aimed to verify, first, if physical parameters were different between positions during official matches in the English Football League Championship. Second, whether game location (home vs. away games) and playing status (full match vs. substitute) affected players' physical performance. Twenty-six, male, professional, football players of the same club were included in this data analysis during the 2023-24 season. STATSports 10 Hz global navigation satellite systems Apex units (Northern Ireland, United Kingdom) were used to monitor official matches (21 games). The metrics recorded were distance covered (m·min-1), high-speed running distance (>19.8 km·h-1), sprint distance (>25.2 km·h-1), the number of accelerations (>3 m·s-2), decelerations (<-3 m·s-2), and high-metabolic-load distance (HMLD) measured in meters (>25.5 w·kg-1). Significant differences were found between positions and game location for distance covered and high-speed running (HSR; p < 0.05) as well as between game location (p = 0.020) for sprinting distance. Differences were found between game location (p = 0.034) for decelerations. Differences were found between positions and game location for HMLD (p < 0.05). Significant difference between full-match players vs. substitutes were found for distance covered (p < 0.001), HSR (p = 0.002), accelerations (p = 0.017), decelerations (p = 0.023), and HMLD (p = 0.008). In conclusion, this study found that physical performance was influenced by players' positions and player status, whereas it found that game location affected a minor number of physical metrics. Therefore, practitioners should be aware that training should be tailored based on the physical demands of the players' positions. Moreover, practitioners and managers need to be aware of the positive impact of substitutions on match intensity.